Doxorubicin increases the susceptibility of brain mitochondria to Ca2+-induced permeability transition and oxidative damage - Cardoso, Susana (2008)
This study was aimed at investigating the effects of subchronic administration of doxorubicin (DOX) on brain mitochondrial bioenergetics and oxidative status. Rats were treated with seven weekly injections of vehicle (sc, saline solution) or DOX (sc, 2 mg kg−1), and 1 week after the last administration of the drug the animals were sacrificed and brain mitochondrial fractions were obtained. Several parameters were analyzed: respiratory chain, phosphorylation system, induction of the permeability transition pore (PTP), mitochondrial aconitase activity, lipid peroxidation markers, and nonenzymatic antioxidant defenses. DOX treatment induced an increase in thiobarbituric acid-reactive substances and vitamin E levels and a decrease in reduced glutathione content and aconitase activity. Furthermore, DOX potentiated PTP induced by Ca2+. No statistical differences were observed in the other parameters analyzed. Altogether our results show that DOX treatment increases the susceptibility of brain mitochondria to Ca2+-induced PTP opening and oxidative stress, predisposing brain cells to degeneration and death